Meeting international self-report muscle strengthening guidelines is associated with better cardiovagal baroreflex sensitivity in adults - Jocelyn Waghorn; Beverly D. Schwartz; Madeline E. Shivgulam; Madeline E. Shivgulam; Yanlin Wu; Yanlin Wu; Derek S. Kimmerly; Myles W. O’Brien; Myles W. O’Brien; Myles W. O’Brien (Frontiers in Sports and Active Living)
Engaging in muscle strengthening activities (e.g., resistance training) at least twice/week is promoted by (Inter)national movement guidelines. Cardiovagal baroreflex sensitivity (cvBRS) reflects the ability to modulate R-R interval in response to changes in systolic blood pressure. Given the current conflicting literature, this study posed to explore the relationship between self-report muscle strengthening frequency and spontaneous cvBRS. 114 adults (62 females; age: 33 ± 19 years, 22% >55 years; body mass index: 24.2 ± 3.7 kg/m2) self-reported their weekly muscle strengthening activity frequencies via the Physical Activity and Sedentary Behaviour Questionnaire. Supine beat-by-beat R-R intervals [electrocardiography; 1.00 ± 0.18 s (0.90–1.50 s)] and systolic blood pressure [via finger photoplethysmography; 116 ± 11 mmHg (93–151 mmHg)] were recorded for 10.7 ± 2.0 min (5.3–14.5 min). Spontaneous cvBRS was assessed using the sequence technique. Data were analyzed using multiple regressions adjusted for age, sex, body mass index. Participants completed 2 ± 2 (0–7) days/week of muscle strengthening activities (56% met guidelines), and average overall cvBRS was 14.9 ± 9.1 (3.1–48.4) ms/mmHg. Higher reported frequencies were positively associated with overall cvBRS (Adjusted R2 = 0.40, p < 0.001; β = 2.24, p < 0.001). Meeting muscle strengthening activity guidelines was associated with improved overall cvBRS (Adjusted R2 = 0.29, p < 0.001; β = 7.68, p < 0.001). All results were unchanged if cvBRS for up-sequences or down-sequences only were used (all, p < 0.001). In conclusion, engaging in muscle strengthening exercises and particularly meeting existing guidelines were associated with better beat-by-beat vagally-mediated blood pressure regulation.